Weaving the river: the poetic power to think about [how] (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
The text presents an account of the researchers' participation as lecturers in the workshop “Weaving the river: games for bodies that write” during the IV Brecht and Education Forum. Starting from the assumption of critical qualitative and radically qualitative research, both proposed a meeting, interventions and performances during the Forum, that intended to turn our gaze to the act of research itself, consider the path we build, [how] we research, who we are and what are the foundations that make us weave the seams and choose the flows of our writings. In line with the Forum, the experience questions the trajectory that our bodies figure in political bodies.
Keywords: research; methodologies; axiology; Jiwasa